Viability of a Frictionless Bearing with Permanent Magnets and HTS Bulks - Arsénio, António (2018)
This paper studies the technical viability of a frictionless rotating bearing model comprising one inner rotor part with discontinuous rings with permanent magnets and one outer stator part with discontinuous rings with high temperature superconducting bulks, distributed on a geometric arrangement that guarantees enhanced levitating and guidance forces using the zero field cooling technique. Extensive Finite Element model simulations were carried out to estimate levitation and guidance forces depending on the air gap dimensions. Eccentricity and axial displacement of the rotor are estimated depending on the external radial and axial forces applied to the rotor. Finally, the proposed design of a viable and feasible frictionless bearing prototype is foreseen.